Blood Group O Protect End-Stage Renal Disease Patients With Dialysis From Coronary Artery Disease - Ye, Zixiang; Wu, Yaxin; Tu, Yimin; Chen, Mulei; Gao, Yanxiang; Shi, Linying; Li, Peizhao; Xie, Enmin; Guo, Ziyu; Li, Qing; Yu, Xiaozhai; Li, Yike; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objective: Our study aims to investigate the role of the ABO blood group in the development and severity of coronary artery disease (CAD) in end-stage renal disease patients with dialysis. Methods: A total of 408 end-stage renal disease patients with dialysis between January 2010 to December 2020 were enrolled including 204 diagnosed CAD patients undergoing coronary angiography for the first time, and baseline characteristics as well as Gensini score were collected. Logistic regression analysis and linear regression analysis were performed to evaluate the relation of ABO blood types to the risk and severity of CAD respectively. Results: Blood group O frequency was significantly low in dialysis end-stage renal disease patients with CAD (25% vs 38.24%) compared with the non-CAD patients and multivariable logistic regression showed blood group O was negatively associated with the risk of CAD (adjusted OR = 0.33, 95%CI = 0.19 to 0.60, P＜0.001) as well as the Gensini score tertiles (adjusted OR = 0.23, 95%CI = 0.11 to 0.49, P＜0.001) compared with A blood group. Blood group A, B and AB were positively associated with the high Gensini tertile compared with O blood group (adjusted OR = 4.26, 95%CI = 2.03 to 8.93, P＜0.001; adjusted OR = 2.39, 95%CI = 1.11 to 5.13, P＜0.05; adjusted OR = 4.33, 95%CI = 1.40 to 13.35, P＜0.05). Likewise, multivariable linear regression results revealed O blood type was negatively associated with the Gensini score (β=-26.129, 95%CI=-40.094 to -12.164, P＜0.001). Conclusion: This case-control study demonstrated blood group O was a potential independent protective factor for the risk and severity of coronary artery disease in dialysis end-stage renal disease patients.